Natural products modulate cell apoptosis: a promising way for treating endometrial cancer - Zhou, Xin; Zeng, Yiwei; Zheng, Runchen; Wang, Yuemei; Li, Tao; Song, Shanshan; Zhang, Su; Huang, Jinzhu; Ren, Yulan (Frontiers in Pharmacology, 2023)
natural products, endometrial cancer, apoptosis, signal pathway, anti-cancer effects.Endometrial cancer (EC) is a prevalent epithelial malignancy in the uterine corpus's endometrium and myometrium. Regulating apoptosis of endometrial cancer cells has been a promising approach for treating EC. Recent in-vitro and in-vivo studies show that numerous extracts and monomers from natural products have pro-apoptotic properties in EC. Therefore, we have reviewed the current studies regarding natural products in modulating the apoptosis of EC cells and summarized their potential mechanisms. The potential signaling pathways include the mitochondria-dependent Apoptotic pathway, endoplasmic reticulum stress (ERS) mediated apoptotic pathway, the mitogen-activated protein kinase (MAPK) mediated apoptotic pathway, NF-κB-mediated apoptotic pathways, PI3K/AKT/mTOR mediated apoptotic pathway, the p21-mediated apoptotic pathway, and other reported pathways. We expect this review to highlight the importance of natural products in treating EC and provide a foundation for developing natural products-based anti-EC agents.